Technology Research and Application on Catalyst Entire Life-cycle Management of Coal Fired Power Plant. (October 2019) - Zhang, Yang; Feng, Qianwei; Li, Sha; Li, Cunwen; Pei, Yukun; Zhu, Yue
Abstract: Along with the comprehensive promotion of flue gas ultra-low emission reconstruction in coal-fired power plants, the stability, reliability and economic efficiency of SCR denitrification facility have emerged. SCR catalyst entire life-cycle management is the key to solving the problem. Given the present situation of the catalyst market, operation and maintenance, third-party service, a SCR catalyst entire life-cycle management technology have been proposed, including catalyst supply, quality control, operation and maintenance, effect optimization, life management and scrap disposal in the entire life-cycle of catalyst. By clarifying the accountability units at different stages, implementing corresponding quality control, operation and maintenance and evaluation and optimization technology, demonstration application suggest that the management technology could give full play to the professional expertise of participant companies, make the denitrification facility stable, reliable and economical, and bring obvious environmental and economic benefit.